2017
DOI: 10.1111/jpr.12182
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐Cultural Comparison of U.S. and Japanese Trainees’ Emotion‐Recognition Ability

Abstract: This study investigated the ability of non-Hispanic White U.S. counseling psychology trainees and Japanese clinical psychology trainees to recognize facially expressed emotions. Researchers proposed that an in-group advantage for emotion recognition would occur, women would have higher emotion-recognition accuracy than men, and participants would vary in their emotion-intensity ratings. Sixty White U.S. students and 60 Japanese students viewed photographs of non-Hispanic White U.S. and Japanese individuals exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…These results are unexpected considering that previous studies have insisted on the ingroup effect in facial recognition tasks (e.g., Elfenbein and Ambady, 2002). However, more recent studies have demonstrated that Japanese raters did not show the ingroup advantage in the perception of facial expressions (Matsumoto et al, 2009;Hutchison et al, 2018). Overall, Japanese people's facial expressions may not necessarily be perceived correctly by ingroup members.…”
Section: Discussionmentioning
confidence: 58%
“…These results are unexpected considering that previous studies have insisted on the ingroup effect in facial recognition tasks (e.g., Elfenbein and Ambady, 2002). However, more recent studies have demonstrated that Japanese raters did not show the ingroup advantage in the perception of facial expressions (Matsumoto et al, 2009;Hutchison et al, 2018). Overall, Japanese people's facial expressions may not necessarily be perceived correctly by ingroup members.…”
Section: Discussionmentioning
confidence: 58%
“…The marked impact of color on emoticons conveying negative emotions can also be related to the specific participant population in the present study, since a display of negative emotions is discouraged in the Japanese culture ( Hutchison et al, 2018 ; Matsumoto, 1992 , 2007 ; Sugimoto & Levin, 2000 ). As a consequence, the Japanese are more anxious in interpersonal contexts and are more vigilant and sensitive to signs of disapproval ( Dailey et al, 2010 ; Ishii et al, 2011 ).…”
Section: Discussionmentioning
confidence: 80%
“…These Angry–Sad and Surprised–Happy confusions may also be explained by a specific facial expression decoding strategy of Japanese observers: unlike Western viewers, whose judgments of facial expressions are dominated by the shape of the mouth, Japanese observers (and those in other Eastern cultures) are more likely to judge facial emotions from the eyes (Gedron, 2017; Hutchison et al, 2018; Jack et al, 2009; Sugimoto & Levin, 2000; Yuki et al, 2007) or eyebrows (Hasegawa & Unuma, 2010). This decoding strategy, or the “own emotional dialect” (Dailey et al, 2010, p. 875), is reflected in the design of conventional Japanese emoticons: the mouth is represented by a straight line, regardless of the conveyed emotion, whereas the emotion valence is conveyed by the eye shape, with capital lambdas standing for “happy eyes” (^_^) and capital Ts for “sad eyes” (T_T) (Park et al, 2013; Takahashi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a facial emotion recognition task, clinical psychologists performed better than psychopharmacologists (Dalkiran et al, 2017 ), suggesting that working more on relational aspects contributed to improving the ability to recognize emotions in facial expressions. In a cross‐cultural study (Hutchison et al, 2018 ), US and Japanese clinical psychology trainees were assessed in their ability to recognize facially expressed emotions. The results showed that there were no group or gender differences.…”
Section: Introductionmentioning
confidence: 99%